Trends in the judiciary : interviews with judges across the globe. Volume four - Wallace, Wendell C.; Berlin, Michael M., 1954-; Das, Dilip K., 1941- (London : Routledge, 2021)
Trends in the Judiciary: Interviews with Judges from Across the Globe, Volume 4, provides much needed insights into the lives, working environments, and social milieus of a select group of judges. These legal luminaries, often viewed as pedantic in their ontology, serve the crucial role of preserving the human rights of individuals from being trampled upon with impunity by governments. This text offers detailed data emanating from the narratives of judges who were interviewed by a wide range of academicians, from emerging and mid-career scholars to professionals and established professors. The narratives of the judges are interspersed with research data and country details in an effort to enhance the knowledge base of the readership. Judges from Asia, Africa, the Caribbean, Europe, the Pacific Islands, New Zealand, North America, and South America all contributed to this text by sharing information on their careers as well as insights as they traversed their profession. The readership of this manuscript will experience the thought processes of judges in relation to gender issues, subtle attempts at juridical control, dealing with powerful criminals, and the lives of judges who have other interests besides "interpreting and applying the law." The international, cross-cultural perspectives presented in this book should be of significant interest to academics, practitioners, students, and those interested in comparative legal studies across the globe, the criminial justice community, and criminologists.
OCLC-licensed vendor bibliographic record.
Keywords: Judges -- Interviews; Lay judges -- Interviews; SOCIAL SCIENCE / Criminology